المدرستان القرآنية والتحضيرية وأثرهما في التّحصيل اللغوي والتّربوي لدى الطفل دراسة مقارنة بين عينات من منطقة سوق أهراس - ابتسام بلقاسم (My University, 2023)
Abstract : The Qur’anic and preparatory schools occupied a great place in the educational community and sparked great controversy and sparked a lot of ink for discussion in magazines, websites, and reality about the preference of these two schools, and the extent of their impact on children in various aspects. research in it still occupies the researchers, and the researcher presented in this topic two parts, a theoretical part in which the two schools and their historical framework were introduced in light of the ongoing reforms, the definition of linguistic achievement and educational achievement, then the determination of the methodological framework for the study and its temporal and spatial receptacles. The second part describes, analyzes and compares the foundations of curricula, materials, time cover, means and evaluation. Then, the study population was examined through samples, which are a group of bonds, and their content was analyzed, then counted, and their stability, honesty, and statistical discharge were confirmed. --------------------------- ملخص: احتلت المدارس القرآنية والتحضيرية مكانة كبيرة في الوسط التعليمي وأثارت جدلا كبيرا وأسالت الكثير من الحبر للنقاش في المجلات والمواقع والواقع حول أفضلية هاتين المدرستين، ومدى تأثيرهما على الأطفال من مختلف النواحي . لذلك مازال البحث فيه يشغل الباحثين ،وقد عرضت الباحثة في هذا الموضوع جزئيين جزء نظري تم فيه التعريف بالمدرستين وإطارهما التاريخي في ظل الإصلاحات الجارية وتعريف التحصيل اللغوي والتحصيل التربوي ثم تحديد الإطار المنهجي للدراسة وما يحمل من أوعية زمانية ومكانية . والجزء الثاني تم فيه الوصف والتحليل والمقارنة بين أسس المناهج والمواد والغطاء الزمني والوسائل والتقويم . ثم تم معاينة مجتمع الدراسة من خلال العينات التي هي عبارة عن مجموعة من السندات وتم تحليل مضمونها ثم احصاءها والتأكد من ثباتها وصدقها وتفريغها إحصائيا. ---------------------- Résumé : Les écoles coraniques et préparatoires ont acquis une grande importance dans le domaine de l'éducation, suscitant un débat intense et suscitant de nombreuses discussions dans les revues, les sites Web et la réalité sur l'avantage de ces deux types d'écoles et leur impact sur les enfants sous divers aspects. C'est pourquoi la recherche dans ce domaine occupe toujours les chercheurs. Dans ce sujet, la chercheuse a présenté deux parties : une partie théorique dans laquelle elle a défini ces deux types d'écoles et leur cadre historique dans le contexte des réformes en cours, a défini l'acquisition linguistique et l'acquisition éducative, puis a défini le cadre méthodologique de l'étude et ses limites temporelles et spatiales. La deuxième partie a consisté en une description, une analyse et une comparaison des bases des programmes, des contenus, des calendriers, des ressources et des